Strategi Efektif dalam Pelatihan dan Pengembangan Sumber Daya Manusia di Lembaga Pendidikan - Aisyah Rachmawati Avivah; Ida Rindaningsih (Jurnal bintang manajemen, 2025)
Training and development of human resources (HR) in educational institutions are crucial for enhancing the quality of education and educators’ ability to face increasingly complex teaching challenges. This study aims to analyze effective strategies for HR training and development in educational settings, using a Systematic Literature Review (SLR) approach. This method was used to identify, evaluate, and summarize key findings from relevant studies on HR training and development in the education sector. The results indicate that competency-based training, the use of technology in learning, and collaborative learning are strategies that have proven effective in improving educators’ performance. However, challenges such as resource limitations, infrastructure, and managerial support pose barriers that need to be addressed to maximize training effectiveness. These findings provide valuable insights for educational institutions in designing more sustainable and relevant training programs in line with evolving educational demands.